2009
DOI: 10.1080/08997760902724472
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Patriotism in Explaining the TV Audience of National Team Games—Evidence From Four International Tournaments

Abstract: In the literature addressing the determinants of TV audiences in sports, both the absolute and relative playing strength of the opponents play a prominent role. Regarding national team competitions, however, this study conjectures that patriotism matters as well. Analyzing the Swiss TV audience at 2 World Cups and 2 European Football Championships, this study finds strong evidence that TV ratings are highly affected by the sizes of the groups of foreign residents affiliated with the teams playing on the field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 26 publications
3
31
2
Order By: Relevance
“…Two studies combine both approaches and analyze TV viewing behavior for games from all participating teams over a multitude of tournaments (m  n context). Nüesch and Franck (2009) analyze Swiss TV audiences for 183 broadcasts of games at two FIFA WCs and two UEFA European Championships between 2000 and 2006. They find that after controlling for the type of game and its importance in the tournament context, "both the expected absolute playing strength of the opponents and patriotism strongly predict the TV figures, whereas outcome uncertainty is irrelevant" (Nüesch & Franck, 2009, p. 7).…”
Section: Literature Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies combine both approaches and analyze TV viewing behavior for games from all participating teams over a multitude of tournaments (m  n context). Nüesch and Franck (2009) analyze Swiss TV audiences for 183 broadcasts of games at two FIFA WCs and two UEFA European Championships between 2000 and 2006. They find that after controlling for the type of game and its importance in the tournament context, "both the expected absolute playing strength of the opponents and patriotism strongly predict the TV figures, whereas outcome uncertainty is irrelevant" (Nüesch & Franck, 2009, p. 7).…”
Section: Literature Surveymentioning
confidence: 99%
“…Our study is conceptually closest to the ones by Nüesch and Franck (2009) and Schreyer et al (2017) because we analyze TV viewership in one country (Russia) for football games played by multiple national teams at multiple EC and WC tournaments (m  n context).…”
Section: Literature Surveymentioning
confidence: 99%
“…Media consumption was measured using a five-item, 7-point media consumption index, similar to the approach used by Livingstone and Markham (2008). Participants were asked how much time, on average, they spent consuming Olympic-oriented print media (reading newspapers and magazines), Olympic-oriented televisual media (watching television), and Olympic-oriented digital media (using the Internet to read blogs=websites and to use=follow social media).…”
Section: Variablesmentioning
confidence: 99%
“…Forrest, Simmons, and Buraimo (2005) found that viewing is highest for games involving the star players in the English Premier League. Nüesch and Frank (2009) studied Swiss ratings of the World Cup and European Championship and found that while the strength of the competition matters, patriotism impacts ratings in national soccer team games. Alavy et al (2010) used minute-by-minute TV viewing during English Premier League games and found that viewers demand Feddersen and Rott (2011) included friendlies in the data, added progression through tournament play as factors in the model, and from a TV business prospective obtained an estimate of the reduction in viewing when the game is broadcast by a private instead of a public network.…”
Section: Introductionmentioning
confidence: 99%